2005
DOI: 10.1136/bjsm.2005.020065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral contraceptives and hormone replacement therapy on bone mineral density in premenopausal and perimenopausal women: a systematic review

Abstract: Seventy five articles on the effect of oral contraceptives and other hormone replacement on bone density in premenopausal and perimenopausal women were reviewed. The evidence was appraised using the Oxford Centre for Evidence-Based Medicine levels of evidence. There is good evidence for a positive effect of oral contraceptives on bone density in perimenopausal women, and fair evidence for a positive effect in ''hypothalamic'' oligo/amenorrhoeic premenopausal women. There is limited evidence for a positive effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 103 publications
1
71
1
3
Order By: Relevance
“…87 Moreover, Liu and Lebrun reviewed studies on the efficacy of estrogen therapy in hypothalamic amenorrhea and concluded that there is limited evidence to support a positive effect of such intervention on BMD. 88 Oral contraceptives will probably maintain bone density in hypoestrogenic, amenorrheic athletes while additionally providing contraception. Furthermore, recent studies demonstrated that the estrogen component in OC exerts a protective role on endothelial function, reducing the cardiovascular risk in amenorrheic athletes.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…87 Moreover, Liu and Lebrun reviewed studies on the efficacy of estrogen therapy in hypothalamic amenorrhea and concluded that there is limited evidence to support a positive effect of such intervention on BMD. 88 Oral contraceptives will probably maintain bone density in hypoestrogenic, amenorrheic athletes while additionally providing contraception. Furthermore, recent studies demonstrated that the estrogen component in OC exerts a protective role on endothelial function, reducing the cardiovascular risk in amenorrheic athletes.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…59,60 Eighty percent of population variability in bone mass is genetically determined, and 20% is explained by environmental factors (nutritional, hormonal, lifestyle and fetal influences). 57,[61][62][63][64][65] Osteoporosis is defined as BMD by T score more than 2.5 SDs below the mean BMD for young adults, and osteopenia as a BMD 1.0-2.5 below the mean BMD for young adults. 66 The terms 'osteopenia' and 'osteoporosis', as defined by BMD, can only be applied to postmenopausal women (as per WHO guidelines).…”
Section: Bone Health In An Backgroundmentioning
confidence: 99%
“…This strain causes deformation of bone. The mechanostat theory proposes that bone is capable of sensing biomechanical strain through an internal "mechanostat", thereby adjusting the level of remodelling accordingly to increase bone accretion (Snow, 1996;Barr & McKay, 1998;Voss, Fadale & Hulstyn, 1998;Kemmler et al, 2006;Liu & Lebrun, 2006). BMD accrual usually protects against osteoporosis and subsequent fractures later on in life, especially in females.…”
Section: Introductionmentioning
confidence: 99%